Audit Opinion Impact On Auditor Switching In Indonesian Stock Exchange Manufacturing Firms Period 2018-2022 - Anike Putri; Febi Febriani (Journal of Accounting Inaba, 2023)
This study investigates the impact of audit opinion on auditor switching within the manufacturing sector of companies listed on the Indonesia Stock Exchange from 2018 to 2022. Employing a quantitative descriptive approach, secondary data extracted from annual reports constitutes the research material. Logistic regression analysis serves as the data analysis model. The findings indicate that, according to statistical tests, audit opinion does not exhibit a significant partial effect on auditor switching among manufacturing sector companies listed on the Indonesia Stock Exchange during the specified period